Table of Content - - (Journal of Educational and Psychological Sciences, 2023)
Table of Content 1. Availability of competencies among teachers of gifted, talented, and creative students in governmental schools in Palestine Mrs. Wafa’ Subhi Mustafa 2. The Degree to Which Computer Teachers at The Secondary Stage Possess Blended Learning Competencies Mrs. Sarah Zaid Al-Otebi, Dr. Ashwaq Abdellah Al-Sahim 3. Challenges of Employing Interactive Simulations in Teaching Science Subjects to Intermediate and Secondary Levels from the Viewpoint of Science Teachers in Madinah Dr. Hanaa Eid Alharbi, Mrs. Basimah Saleem Alofi 4. The degree of employing electronic management skills among public school principals in The West Bank provinces from their Perspectives Mrs. Alaa Radi Nasser, Dr. Hussam Husni Al-Qasem 5. Difficulties in providing support services for female students with intellectual disabilities from the point of view of intellectual education teachers in Buraydah City Mrs. Salma Abdulrahman Al Bin Hamad 6. Sexual features Among individuals with Autism Disorder and the way of Dealing with them from parents and care workers Dr. Seham Reyad Alkhuffash 7. Future Anxiety and Problem-Solving Skills as Predictors of Suicidal Ideation among Female University Students Mrs. Raghad Saleh Al-Mufyid, Dr. Ahmed Ali Al-Homaidhi